Serotypes of E. Coli from piglets with diarrhoea - ΚΥΡΙΑΚΗΣ Σ.; ΣΑΡΡΗΣ Κ.; ΣΙΜΟΣ Ε.; ΑΝΔΡΕΩΤΗΣ Ι.; ΤΣΑΛΤΑΣ Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
An attempt was made to serotype 102 E.coli strains isolated from diarrhoic pigs aged from 2 days to 8 weeks in a commercial pig farm in Central Greece. A total of 8 serologic groups from 36 strains were found in the following order: 0149 (17 strains), 0141 (6), 08 (4), 0115 (4), 010 (1), 085 (1), 0139 (1), and 045 (1). Six out of 15 strains tested were found capable of producing heat stable (ST) enterotoxin. From the typed groups 86.1% of the strains were hemolytic. The group 010 was found for the first time in Greece